E-5: UNVEILING THE PATHWAY TO NEWCOMERS’ AFFECTIVE COMMITMENT: : EXPLORING THE SEQUENTIAL IMPACT OF SOCIAL CAPITAL RESOURCES AND PERCEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL SOCIALIZATION TACTICS - Ajmal, Muhammad; Ijaz, Bilal; Khan, Imran (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
This research article investigates the intricate interplay between affective commitment, organizational socialization tactics, social capital resources, and perceived organizational support in the context of newcomer integration within organizations. Recognizing the paramount significance of newcomers’ rapid assimilation into the organizational culture, this study aims to elucidate the sequential mediating role of social capital resources and perceived organizational support in enhancing affective commitment through effective organizational socialization tactics. Drawing upon a diverse array of theoretical foundations, including social exchange theory and organizational socialization literature, this research employs a quantitative methods approach. Quantitative data analysis utilizes structural equation modeling to examine the serial mediation process. The outcomes of this study offer novel insights into the mechanisms underpinning newcomers’ affective commitment development, shedding light on how social capital resources and perceived organizational support synergistically bolster the effects of organizational socialization tactics. These findings not only contribute to the theoretical advancement of organizational socialization and commitment literature but also provide practical implications for organizations seeking to optimize the integration of newcomers for enhanced employee engagement and long-term commitment.